Perencanaan Media Sosial Dalam Sosialisasi Surat Pemberitahuan Tahunan (Spt) Tahun 2020 - Bagas Sakti Dewabrata (Universitas Gadjah Mada, 2022)
Annual Tax Return (SPT) is a letter that is used by taxpayers to report tax calculations, tax payments, tax objects or non-tax objects, as well as assets and liabilities in accordance with the provisions of tax laws. In 2020, twitter accounts, Instagram, Facebook and Youtube The Directorate General of Taxes of the Republic of Indonesia conducted socialization about the Annual Tax Return (SPT) which aims to provide socialization to the wider community to immediately report their SPT. The purpose of this research is to see how social media planning is carried out by the Directorate General of Taxes in terms of socializing the Annual Tax Return (SPT) through social media. The main theory used in this research is the social media planning theory according to Steiner. This research is a qualitative research using a case study research method. Data collection was carried out by in-depth interviews with the social media team from the Directorate General of Taxes of the Republic of Indonesia. The main finding of this research is that social media planning is carried out through a basic approach and follows the four elements of Steiner's social media planning theory, namely types of solutions available, planning, social mechanics, and implementations.